ISLAMIC E-COUNSELING THERAPY SERVICES FOR TEENAGE PSYCHOLOGIST VICTIMS OF SEXUAL ABUSE (Universitas Islam Negeri Mataram, 2024)
Sexual harassment is nothing new, we have heard news that for many years, women have received treatment that is disrespectful to their hearts and selves. Recently, there have been many cases of women experiencing harassment and sadly it was carried out by relatives and people in their life environment. This bad treatment was carried out by people who were supposed to protect themselves from various threats from the outside world, but it was the people closest to them who were the perpetrators of the sexual harassment. Counseling services for the psychology of adolescent victims of sexual abuse are carried out using descriptive qualitative methods. with direct involvement, the type of approach is phenomenology. There are several implementation series consisting of activity matrices, starting from the preparation stage to the closing stage. Islamic Counseling service activities based on the e-Counseling Islamic Therapy (CIT) application help reduce the psychological pressure on adolescent victims of sexual harassment in the Regional Technical Implementation Unit for the Protection of Women and Children in Bogor City. E-counseling services are needed to facilitate counselees in the counseling process so that the application helps in handling it as a medium. Counseling is carried out in several meeting sessions that have been agreed upon with the counselee and counselor/psychologist. The counseling process is carried out systematically based on the guidelines and techniques that already exist in the counseling application. There were 9 meetings in this counseling session using the individual counseling method.